Verifikasi penentuan kadar unsur-unsur kelumit esensial dalam bahan makanan dengan analisis pengaktifan neutron - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Psikologi Universitas Gadjah Mada, 1998)
ABSTRACT A research has been conducted to determine the essential trace elements (Mn, Cr, Fe and Zn) which is contained in potatoes (Solanum tuberosum Sp.) and peanuts (Arachis hypogeae Sp.) using Neutron Activation Analysis (NAA) method. For the purpose of verification of the determination results, a curve fitting analysis of the gamma spectrum peaks of those elements has been done. The netto peak area ratios of PCA Nucleus to curve-fitting results were between 0,08% and 5,59%. Meanwhile the element concentration ratios of PCA Nucleus computation to curve-fitting results were between 0,12% and 22,09%.